Życie wartościowe w percepcji studentów z niepełnosprawnością - Otapowicz, Dorota; Sakowicz-Boboryko, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2024)
The perception of students with disabilities as young people with personal potential that they wish to develop draws attention to the meanings they give to their aspirations and daily relationships, creating their own vision of a worthwhile life. The aim of the research was to identify the values that students with disabilities wish to follow in making their lives worthwhile and fulfilling. The research material was obtained by means of free interviews conducted with ten students. The content of the students’ statements was analysed and interpreted, looking for the main areas and specific values they see in their lives. Three visions of a valuable life based on the beliefs of students with disabilities emerged. The first vision revolves around the importance of social relationships, especially close bonds. The second vision is driven by the desire for achievement and the resulting personal satisfaction. The third vision emphasises the importance of experiencing happiness and enjoying every moment of life. Each of these was associated with distinct orientations of the aspirations and expectations of students with disabilities, assessing what is worth striving for, what they desire and what values they follow.